Expecting the Unexpected: Emissions Uncertainty and Environmental Market Design - Borenstein, Severin; Bushnell, James; Wolak, Frank A.; Zaragoza-Watkins, Matthew (American Economic Review, 2019)
We study potential equilibria in California’s cap-and-trade market for greenhouse gases (GHGs) based on information available before the market started. We find large ex ante uncertainty in business-as-usual emissions and in the abatement that might result from non-market policies, much larger than the reduction that could plausibly occur in response to an allowance price within a politically acceptable range. This implies that the market price is very likely to be determined by an administrative price floor or ceiling. Similar factors seem likely to be present in other cap-and-trade markets for GHGs. (JEL D47, D81, Q54, Q58, R11)